2022
DOI: 10.1155/2022/2466817
|View full text |Cite
|
Sign up to set email alerts
|

Inner Product Fuzzy Quasilinear Spaces and Some Fuzzy Sequence Spaces

Abstract: It has been shown that the class of fuzzy sets has a quasilinear space structure. In addition, various norms are defined on this class, and it is given that the class of fuzzy sets is a normed quasilinear space with these norms. In this study, we first developed the algebraic structure of the class of fuzzy sets F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, in [17,18] we gave examples of how quasilinear spaces can be used in signal processing. In addition, normed and Hilbert quasilinear space examples of some fuzzy number sets are given in [19] and their properties are examined. A recent study on qasilinear spaces is the concept of quasi-algebra its details can be found in [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [17,18] we gave examples of how quasilinear spaces can be used in signal processing. In addition, normed and Hilbert quasilinear space examples of some fuzzy number sets are given in [19] and their properties are examined. A recent study on qasilinear spaces is the concept of quasi-algebra its details can be found in [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Then, quasilinear inner product spaces, generalizations of inner product spaces, were defined to develop quasilinear functional analysis in [7][8][9][10]. In addition, Yılmaz et al [11] demonstrated that Hilbert quasilinear spaces are a special class of fuzzy number sequences. In [12,13], Levent and Yılmaz included some quasilinear applications, such as signal processing.…”
Section: Introductionmentioning
confidence: 99%